The effects of illness perception on death anxiety and satisfaction with life in patients with advanced gastrointestinal cancer - Bahçecio?lu Turan, Gülcan; Türkben Polat, Hilal (Cambridge University Press, 2024)
Objectives This study was conducted to determine the effects of illness perception on death anxiety and satisfaction with life in patients with advanced gastrointestinal cancer. Methods This cross-sectional and correlational study was conducted with 125 patients with cancer who were admitted to the oncology clinic of a university hospital in the Central Anatolian Region of Turkey between March and December 2022 and who met the research criteria and accepted to participate in the study. The data were collected with Patient descriptive information form, Brief Illness Perception Questionnaire (BIPQ), Scale of Death Anxiety (SDA), and Satisfaction with Life Scale (SWLS). Results It was found that mean BIPQ score of the patients was 39.54 ± 12.82, the mean SDA score was 8.02 ± 3.16, and the mean SWLS score was 14.74 ± 5.19. BIPQ total score was found to affect SDA total score positively (? =.751) and SWLS total score negatively (? = -.591). SDA total score was found to affect SWLS total score negatively (? = -.216) (p <.05). Significance of results It was found that patients with advanced gastrointestinal cancer had moderate level of illness perception and life satisfaction, and high death anxiety. It was found that as illness perception of the patients increased, their death anxiety increased and satisfaction with life decreased. In addition, it was found that as the death anxiety of patients increased, their satisfaction with life decreased. © 2023 The Authors. Published by Cambridge University Press.
Keywords: Advanced stage; Death anxiety; Gastrointestinal cancer; Illness perception; Patient; Satisfaction with life